REDESAIN VISUAL IDENTITY 2R HANDY CRAFT SEBAGAI UPAYA PENINGKATAN BRAND IMAGE DAN PROMOSI: Muhammad Divo Bramasta, Ade Moussadecq - Divo Bramasta, Muhammad; Moussadecq, Ade (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Paramadina, 2024)
2R Handy Craft is an MSME that operates in the field of fashion and souvenirs typical of Lampung. As a growing MSME. 2R Handy Craft has a logo that contains elements of plagiarism which can be detrimental and hinder the development of 2R Handy Craft itself, as well as inappropriate promotional media in introducing and offering products from 2R Handy Craft. This redesign uses the morphological method as a creative method to formulate the visual concept of a design. The morphological method was used to redesign the brand image of 2R Handy Craft so that it could create a strong logo visualization to represent the brand image of 2R Handy Craft. Logo design begins with collecting visual data, verbal data, analysis, visual concepts, finalizing the design and then supporting it with promotion through main and supporting media. The result of this redesign is a logo and philosophy which is applied to the main media, namely standard manual graphics, then assisted by supporting media, namely Instagram, stationary set, vehicle design and so on.